Behavioral Insights for Development : Cases from Central America - Calvo-González, Oscar; Zoratto, Laura (World Bank, Washington, DC, 2017)
Behavioral Insights for Development: Cases from Central America brings together a set of experiences that applied behavioral insights to different areas of public policy—in some cases through randomized control trials, and in others using surveys or behavioral games. These experiences collectively show the promise of public policies that are informed by a better understanding of what drives individual behavior.